Production Technology for Adding GDL (Glucono Delta Lactone) to Soy-Based Foods - Athila Safira Rahma (Research Collaboration Community (RCC), 2021)
The technology of adding Glucono Delta Lactone (GDL) to food made from soybeans is gaining popularity because it has many advantages. GDL is an acid that functions to coagulate proteins. GDL is a food additive that is Generally Recognized as Safe (GRAS). GDL has been applied in soy-based products such as tempeh and tofu. The use of GDL in tempeh products can reduce the acidification time of tempeh to 2-3 hours so that the production capacity of tempeh can increase significantly and reduce the amount of water used in the production process. The use of GDL in tofu is as a coagulant which makes the quality of tofu better than other agglomerates. The main objective of this paper is to provides an explanation of the application of GDL to soy-based foods. So, GDL can be used as an innovation to develop soybean-based food industries. It begins from describing about GDL, provides comparison between natural soy-based food and soy-based foods with GDL from study literature. Then moves to the application of GDL in tempeh, the application of GDL in tofu, and Back-Slopping technology.